Analysis of Influence of Stiffness Variation on Uniform Load Characteristics of the Planetary Gear Trains - Li Kaiyang; Li Aiguo; Lin Ruiyi; Shi Lubing; Yan Shidang; Liu Zhongming (Jixie chuandong)
In this study, a three-dimensional model of the planetary gear train with straight cylindrical gears is established, and a virtual prototype model is constructed by using dynamics simulation software. Through the dynamics analysis, the accuracy and feasibility of the virtual prototype simulation model are verified. The study shows that the supporting stiffness of each component in the transmission system has a significant effect on the uniform load characteristics, and the change of the supporting stiffness of the planetary gear has the most sensitive effect on the uniform load characteristics. The uniform load characteristics of the transmission system is not sensitive to the change of the flexible supporting stiffness of the sun gear, but it is more sensitive to the change of the flexible supporting stiffness of the planetary gear, and the uniform load coefficient has obvious changes. The effect of gear tooth meshing stiffness changes on the uniform load characteristics of the transmission system is independent, simultaneously reducing the internal and external meshing stiffness has a more obvious uniform load effect than reducing the meshing stiffness alone.